STRATEGIC APPROACH TO TALENT MANAGEMENT: A THEORETICAL MODEL - Kalaiselvan, K; Nachimuthu, KP (Journal of Contemporary Research in Management (JCRM), 2017)
â€œWe must view talent management programs as part of a bigger picture, not in isolation. It is the elements of this bigger picture, the interconnected cycle, which will make or break success.â€ -Â Â Â Â Â Â (HRD â€“ Unisys Asia Pacific, 2005) Â Many organizations struggle to show how the talent management processes they support are relevant to driving their business success / to their business strategy. Rather than being viewed as a critical part of business strategy execution, talent management is viewed as a mere administrative function that is necessary but relatively uninteresting to business operations and success. Talent management processes in many companies should be viewed has a heart in a body. Heart is a crucial for a survival, better the care taken, better will be the life/health. The same sort of thing might be said about talent management processes too (used for performance management, staffing, development compensation, and succession). Many appreciate the importance of these processes for running a stable company, but they do not see them as tools for driving business strategy execution. This is unfortunate because the problem is many organizations do not understand the relationship between talent management processes and business goals. If understand / done correctly, talent management is about putting the right people in the right jobs doing the right things in the right way and in right development. Research demonstrates that companies with enlightened talent management policies have higher returns on sales, investments, assets and equity (Caudron, 2001).This paper will discusses how to use talent management processes to drive business execution. The model and matrixes proposed in this paper is not about implementing new talent management processes. It is about how to use existing processes in a more integrated and focused manner so that they can give a greater relevance and impact on operational business strategy and the derived results out of it. Â